Pengaruh Metode Game Based Learning Terhadap Minat Belajar Siswa pada Mata Pelajaran Matematika di Kelas V SDN 060799 Medan Labuhan - Safrida, Safrida; Harahap, Syarifah Ainun; Ramadhan, Nuri (Medan Resource Center, 2024)
This study employs an experimental research design to determine the effect of using the Game-Based Learning model on students' learning outcomes in spatial building materials. The research uses a True-Experimental Design with a Posttest Only Control Group Design approach. The population includes all fifth-grade students from SDN 060799 Medan Labuhan, consisting of two classes, Class V A and Class V B. Sampling was conducted using a simple random sampling technique. The results show that the average posttest score in the experimental group, which used the Game-Based Learning model, was 76, while the control group scored 70.95. Hypothesis testing using an independent sample t-test yielded a t-value of 2.072, which is greater than the critical value of t-table (1.684), with a significance level of 0.044 (p < 0.05). These findings indicate that the Game-Based Learning model has a significantly greater impact on student learning outcomes compared to conventional methods.